Contemporary screen time modalities among children 9–10 years old and binge‐eating disorder at one‐year follow‐up: A prospective cohort study. Issue 5 (1st March 2021) - Nagata, Jason M.; Iyer, Puja; Chu, Jonathan; Baker, Fiona C.; Pettee Gabriel, Kelley; Garber, Andrea K.; Murray, Stuart B.; Bibbins‐Domingo, Kirsten; Ganson, Kyle T.
Abstract: Objective: To determine the prospective associations between contemporary screen time modalities in a nationally representative cohort of 9–10‐year‐old children and binge‐eating disorder at one‐year follow‐up. Method: We analyzed prospective cohort data from the Adolescent Brain Cognitive Development (ABCD) Study ( N = 11, 025). Logistic regression analyses were conducted to estimate associations between baseline child‐reported screen time (exposure) and parent‐reported binge‐eating disorder based on the Kiddie Schedule for Affective Disorders and Schizophrenia (KSADS‐5, outcome) at one‐year follow‐up, adjusting for race/ethnicity, sex, household income, parent education, BMI percentile, site, and baseline binge‐eating disorder. Results: Each additional hour of total screen time per day was prospectively associated with 1.11 higher odds of binge‐eating disorder at 1‐year follow‐up (95% CI 1.05–1.18) after adjusting for covariates. In particular, each additional hour of social networking (aOR 1.62, 95% CI 1.18–2.22), texting (aOR 1.40, 95% CI 1.08–1.82), and watching/streaming television shows/movies (aOR 1.39, 95% CI 1.14–1.69) was significantly associated with binge‐eating disorder. Discussion: Clinicians should assess screen time usage and binge eating in children and adolescents and advise parents about the potential risks associated with excessive screen time.